Influence of Polyether Backbone PEO-PPO on the Drug Release Behavior of Polyurea Xerogels - Julia G. Vargas; Heber E. Andrada; Bruno A. Fico; Julia M. Paulino; Natália N. Silveira; Raquel A. dos Santos; Eduardo F. Molina (MDPI AG, 2023)
To evaluate possible structural changes and thermal stability of the polyurea unloaded and loaded with diclofenac sodium, polyurea networks based on polyetheramine containing polypropylene oxide (PPO) or polyethylene oxide (PEO) and hexamethylene diisocyanate trimer-HDI were synthesized. The formation of the network was controlled by sol-gel reactions, and the obtained materials were then characterized by different techniques (FTIR, XRD, TGA). Moreover, the amount of diclofenac released could be modulated as a function of time, studying the water absorption or swelling capacity, the cytotoxicity of the material and the amount of drug released. A choice was therefore made on the hydrophilicity of PEO- or PPO-based polyetheramine (with similar molecular weight), and the release profile was hereafter correlated with the water absorption by the PEO/PPO polyurea matrix. Links could finally be established between the release of diclofenac and the polyurea matrices properties, such as the nature of polymer (PEO/PPO) and the hydrophilicity (water uptake). Our objective here is to identify challenges and opportunities for the development of innovative functional biomaterials for health applications.